2000
DOI: 10.1126/science.287.5458.1655
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Pathogenicity Island 2-Dependent Evasion of the Phagocyte NADPH Oxidase

Abstract: A type III protein secretion system encoded by Salmonella pathogenicity island 2 (SPI2) has been found to be required for virulence and survival within macrophages. Here, SPI2 was shown to allow Salmonella typhimurium to avoid NADPH oxidase-dependent killing by macrophages. The ability of SPI2-mutant bacteria to survive in macrophages and to cause lethal infection in mice was restored by abrogation of the NADPH oxidase-dependent respiratory burst. Ultrastructural and immunofluorescence microscopy demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
423
2
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 519 publications
(446 citation statements)
references
References 43 publications
10
423
2
5
Order By: Relevance
“…In macrophages, Salmonella inhibit the fusion of SCV with endosomes and lysosomes 128 and prevent the localization of NADPH oxidase 129,130 and Nos2 131 with SCVs, thereby protecting the bacteria from the microbicidal effect of ROI and RNI.…”
Section: Nadph Oxidase and Nos2mentioning
confidence: 99%
“…In macrophages, Salmonella inhibit the fusion of SCV with endosomes and lysosomes 128 and prevent the localization of NADPH oxidase 129,130 and Nos2 131 with SCVs, thereby protecting the bacteria from the microbicidal effect of ROI and RNI.…”
Section: Nadph Oxidase and Nos2mentioning
confidence: 99%
“…In vitro studies, using different host cell types, have shown that S. typhimurium replicates intracellularly within Salmonella-containing vacuoles (SCVs) apparently protected from host cell antimicrobial activities (Buchmeier and Heffron, 1991;Rathman et al, 1997;Vazquez-Torres et al, 2000). Genetic studies have led to the identification of a large number of genes necessary for intracellular survival.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Neisseria gonorrhoeae does not prevent O 2 Ϫ generation but prevents extracellular release of O 2 Ϫ , thus allowing extracellular neisseriae to survive (16). On the other hand, Salmonella enterica serovar Typhimurium does not prevent O 2 Ϫ generation but blocks release of O 2 Ϫ in salmonella-containing vacuoles, so that intracellular salmonellae can survive (23). Luminol is a small membrane-permeable molecule that can be used to measure total (intra-and extracellular) O 2 Ϫ production (8).…”
Section: Upon Exposure To Neutrophils the Hge Agent Did Not In-mentioning
confidence: 99%